Nurses’ performance in the area of incontinence: we can do more (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
I would like to invite you to reflect on the work of our estimated stomatherapy, in the area of incontinence. Or, as I prefer to refer to it, the area of urinary and evacuation dysfunctions, understanding that dysfunctions go beyond urinary or fecal loss, also contemplating urinary retention and intestinal constipation.